Highland lady eaudiobook - Faulkner, Colleen (Scottish Fire, 2011)
Colleen Faulkner is a name synonymous with medieval romance. In Highland Lady, Elen Burnard makes a deathbed promise to her father to protect the estate and reclaim valuable lands that were stolen from the family centuries before. Determined to keep her word, Elen rules the land with an iron fist, until the day her sister is kidnapped by the Forrest family. To ensure her sister's safe return, Elen kidnaps Lord Munro Forrest, and while she awaits the exchange of his life for her sister's, more than her promise is in jeopardy.